A new adaptive slip-slide control system for railway vehicles. (October 2018) - Çimen, Mehmet Ali; Ararat, Öncü; Söylemez, Mehmet Turan
Highlights: Slip-slide control method eliminating drawbacks of existing approaches is proposed. Dynamic analysis of phase shift of traction system including adhesion model is done. Control method is transformed into an adaptive form using the outcomes of analysis. Comparative test study with the existing successful approaches is conducted. Abstract: In railway transport, braking and traction forces mainly depend on the normal force and the adhesion coefficient between the wheel and the rail. Regarding the restrictions on controlling the normal force, maximization of adhesion coefficient seems to be the only way of increasing braking and tractive efforts. Moreover, efficient utilization of adhesion can also reduce operating costs with avoiding early wheel and rail damages and minimizing the trip time. On the other hand, adhesion between the rail and the wheel is a highly dynamic function of many parameters such as environmental conditions, speed and slip ratio. Unfortunately, there is not any sufficiently accurate and reliable way of obtaining these parameters yet. Recently, an event based control scheme has been presented to maximize adhesion utilization without necessitating any of the above-mentioned parameters. This method provides efficient utilization of adhesion and eliminates problems (e.g. reliability, stability, continuous excitation of traction system and slow recuperation detection time) that are faced with the previously developed approaches. In this paper, dynamics of phase shift between the input and the output of the traction system is analyzed and an adaptive form of the recently proposed event based control scheme is constructed in order to further develop the adhesion utilization. Results obtained with the adaptive approach are compared with the conventional form of the control scheme as well as experimentally proven and industrially applied two successful methods for different driving scenarios and wheel-rail conditions.